Dispersion and Nonlinearity Distortion Compensation of the QPSK/16QAM Signals Using Optical Phase Conjugation in Nonlinear SOAs - Aneesh Sobhanan; Lakshmi Narayanan Venkatasubramani; R. David Koilpillai; Deepa Venkitesh (IEEE Photonics Journal, 2020)
We experimentally demonstrate the simultaneous compensation of both dispersion and nonlinear effects in a 100 km optical fiber link using optical phase conjugation of a 21 GB aud QPSK and 16QAM signal with nonlinear SOAs. Error-free performance is recorded for a launched power of up to 12 dBm, without any digital signal processing to compensate for distortions due to chromatic dispersion and nonlinear effects in fiber. The performance is verified for operation across the C-band.